Perkembangan Kurikulum Multikultural di Sekolah Dasar: Menyongsong Tantangan Global - Juliana Margareta Sumilat; Virginia A. Tuwaidan (Journal on Education, 2024)
Multicultural curriculum in elementary schools is an important focus in the current global education context. This research describes the developments and challenges related to the implementation of a multicultural curriculum at the elementary level, especially in anticipating global challenges. Through a literature review of related literature, this study identifies various approaches, strategies and issues that arise in the course of a multicultural curriculum in elementary schools. The literature study highlights the importance of awareness of cultural, ethnic and social diversity in the curriculum, as well as how this approach can integrate global perspectives in learning. In addition, challenges such as cultural resistance, development of relevant learning materials, and teacher training are the main highlights in efforts to realize an effective multicultural curriculum. The results of this study provide in-depth insight into the evolution of multicultural curricula in elementary schools, as well as highlighting the efforts needed to address global challenges such as migration, globalization and cultural diversity. The implications of these findings for educational practice will be discussed to strengthen the implementation of a multicultural curriculum that is more holistic and responsive to current global realities in elementary schools.